CD137L Signaling is an Inflammation Checkpoint in Renal Inflammation. (July 2018) - Lee, Jong Soo; cho, Hong Rae; Kwon, Byungsuk; Park, Kyung Sun; Kim, Juyang; Kim, Hyejung; Park, Sangjoon
Abstract : We have previously shown that signaling via CD137 ligand (CD137L) promotes renal inflammation occurring after ischemia-reperfusion injury by inducing production of neutrophil-recruiting chemokines from tubular epithelial cells. In this study, we provide evidence showing that CD137L signaling enhances resolution of renal inflammation and renal tissue repair. Administration of CD137-Fc fusion protein 24 hours after renal ischemia-reperfusion injury increased Arginase-expressing macrophages and proliferation of tubular epithelial cells. RNA seq analysis of bone marrow-derived macrophages (BMDMs) showed decreased expression of inflammatory genes and increased expression of anti-inflammatory genes. Interestingly, GM-CSF and CD137-Fc synergistically suppressed transcription-controlling genes and promoted transcription of genes involved in negative regulation of cell proliferation. RNA seq analysis also demonstrated the rewiring of glycolysis and TCA cycle by GM-CSF and CD137L co-signaling in BMDMs. Finally, we showed that absence of CD137L signaling had uncontrollable chronic renal inflammation in the unilateral ureteral obstruction model. Taken together, our results suggest that CD137L signaling is critical in resolution of tissue inflammation.